Institution-wide peer mentoring: Benefits for mentors - Beltman, Susan; Schaeben, M. (Queensland University of Technology, 2012)
Extensive research has shown the benefits of mentoring, including peer mentoring, for higher education students, especially in their first year. However, few studies have focussed exclusively on the outcomes for the mentors themselves. This paper reports the findings of data gathered over three years about a university-wide peer mentoring program. Benefits identified by 858 mentors were coded inductively and four major categories emerged: altruistic, cognitive, social and personal growth. The findings have implications for the promotion of mentor programs to administrators and to prospective mentors. The study provides evidence that university-wide peer mentoring programs offer multiple positive outcomes for the mentors involved, and potentially for higher education institutions administering and supporting such programs.